THE RELATIONSHIP BETWEEN KNOWLEDGE AND COMPLIANCE LEVELS IN TAKING IRON TABLETS AMONG ADOLESCENT GIRLS (Proceedings OPTIMAL, 2024)
Fe tablets have many benefits for adolescent girls including maintaining and increasing concentration of learning, creating more enthusiastic activitiea, as well as improving memory and learning ability at school. The result of the study conducted at the Adolescent Integrated Healthcare Post (Posyandu) found that 6 out of 10 adolescents did not know about the importance of balanced nutritional intake to prevent anemia and did not routinely take Fe tablets, especially during menstrual periods. This study aims to determine the relationship between knowledge and the level of compliance with taking Fe tablets among adolescent girls at the Adolscent Posyandu. This was a quantitative study with a cross sectional approach. The study population involved all adolescent girls at posyandu as many as 2227 people and the sample size of 96 adolescents were selected using proportional to size technique. The data collection instrument was a questionnaire. Data were analyzed using univariate analysis with frequency distribution and bivariate analysis with chi square test. Less than half (34.3%) of adolescents had poor level of knowledge on Fe tablets and less than half (47.9%) of adolescents had low level of compliance with taking Fe tablets. There was a relationship between knowledge and the level of compliance with taking Fe tablets anong adolescent girls at posyandu with a p value=0.000. It is recommended that healthcare workers through Posyandu conduct counseling activities to adolescents about the benefits of Fe tablets on an ongoing basis to increase their knowledge and compliance in consuming Fe tablets. Furthermore, adolescents are expected to increase their insight by accessing information media or by consulting healthcare workers.